Progress in nano-electro-optics VI : nano-optical probing, manipulation, analysis, and their theoretical bases - Ohtsu, Motoichi. (Springer, 2017)
This volume focuses on nano-optical probing, manipulation, and analysis. It begins with recent developments in near-field optical spectroscopy that clarify quantum states at the nanoscale, followed by a theory for a photon-electron-phonon interacting system at the nanoscale. Further topics include: visible laser desorption/ionization mass spectroscopy exhibiting near-field effects; a practical nanofabrication method with optical near fields applied to a SHG device; a theory and experimental achievements on optical transport of nanoparticles, selectively manipulated by resonant radiation force. Taken as a whole, this overview will be a valuable resource for engineers and scientists working in the field of nano-electro-optics.